ZULFIYANING “BAHOR KELDI SENI SOG’INIB” SHE’RI BADIIY TAHLILI - Maqsudova Odina Mutalipxon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article presents an artistic analysis of one of the most famous poems of the poetess Zulfia. Each clause of this poem is discussed separately. It is known that Hamid Olimjon and Zulfiya’s works are closely related. This article also talks about this connection. In the article, Zulfiya’s feelings are expressed based on the poem.